Marijuana medicalization and motor vehicle fatalities: a synthetic control group approach - Bartos, Bradley (Journal of experimental criminology, 2020)
This paper reports a quasi-experimental evaluation of California’s 1996 medical marijuana law (MML), known as Proposition 215, on statewide motor vehicle fatalities between 1996 and 2015.